2019
DOI: 10.1101/814608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Up-regulation of autophagy by low concentration of salicylic acid delays methyl jasmonate-induced leaf senescence

Abstract: 15Crosstalk between salicylic acid (SA) and jasmonic acid (JA) signaling plays an important 16 role in molecular regulation of plant senescence. Our previous works found that SA could 17 delay methyl jasmonate (MeJA)-induced leaf senescence in a concentration-dependent 18 manner. Here, the effect of low concentration of SA (LCSA) application on MeJA-induced 19 leaf senescence was further assessed. High-throughput sequencing (RNA-Seq) results 20 showed that LCSA did not have dominant effects on the genetic regu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…A group of metabolites that separated stand 1 from the others was phenolic acids: salicylic acid, benzoic acid, and caffeic acid that increased in response to girdling in stand 1 and decreased in the other stands (Figure 7C) indicating that salicylic acid may be involved in the regulation of senescence in aspen. One possible explanation is that elevated salicylic acid levels may avert girdling‐induced senescence in stand 1 due to its antagonistic effect on the jasmonate signaling pathway (Miao & Zentgraf, 2007; Van der Does et al, 2013; Yin et al, 2020), that could be activated by girdling, based on the enhanced expression of PR3 ( PATHOGENESIS RELATED PROTEIN 3 , Potra001809g14625, log 2 fc 3.88) and repressed expression of JAZ8 ( JASMONATE‐ZIM‐DOMAIN PROTEIN 8 , Potra004547g25056, log 2 fc − 1.51), a repressor of jasmonic acid signaling (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A group of metabolites that separated stand 1 from the others was phenolic acids: salicylic acid, benzoic acid, and caffeic acid that increased in response to girdling in stand 1 and decreased in the other stands (Figure 7C) indicating that salicylic acid may be involved in the regulation of senescence in aspen. One possible explanation is that elevated salicylic acid levels may avert girdling‐induced senescence in stand 1 due to its antagonistic effect on the jasmonate signaling pathway (Miao & Zentgraf, 2007; Van der Does et al, 2013; Yin et al, 2020), that could be activated by girdling, based on the enhanced expression of PR3 ( PATHOGENESIS RELATED PROTEIN 3 , Potra001809g14625, log 2 fc 3.88) and repressed expression of JAZ8 ( JASMONATE‐ZIM‐DOMAIN PROTEIN 8 , Potra004547g25056, log 2 fc − 1.51), a repressor of jasmonic acid signaling (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation is that elevated salicylic acid levels may avert girdling-induced senescence in stand 1 due to its antagonistic effect on the jasmonate signaling pathway (Miao & Zentgraf, 2007; Van der Does et al, 2013;Yin et al, 2020), that could be activated by S1).…”
Section: Salicylic Acid Metabolism Is Affected By Stem Girdlingmentioning
confidence: 99%
“…The studies on SA dihydroxylases, SA 3-HYDROXYLASE (S3H) and S5H, showed that SA is involved in both the onset and the progression of leaf senescence (Zhang et al 2013(Zhang et al , 2017b. In addition, SA has been shown to promote leaf senescence by inducing autophagic lysosome formation (Yoshimoto et al 2009;Xiao et al 2010;Yin et al 2020). It is well recognized that SA plays a direct role in both the onset and progression of leaf senescence, but most of these results are from Arabidopsis studies.…”
Section: Salicylic Acidmentioning
confidence: 99%
“…In the senescence stage, leaves degenerate and rearrange nutrients accumulated during the growth stage to sink parts such as seeds, assisting the plant in productivity and fitness. Protein autophagy plays a central role in leaf senescence (Yin et al ., 2020). Here, using the RNA‐Sequencing data (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE43616) (Woo et al ., 2016) from GEO (Edgar et al ., 2002) for the entire lifespan of Arabidopsis leaves, we explored how the genes encoding ARMs are regulated during the senescence stage, which to a large extent reflects the process of protein autophagy.…”
Section: Resultsmentioning
confidence: 99%